In situ Photosynthetic Activities and Associated Biogeochemical Changes in Three Tropical Seagrass Species - Purvaja, Ramachandran; Ganguly, Dipnarayan; Hariharan, G.; Arumugam, K.; Ramesh, R. (Frontiers in Earth Science, 2020)
Tropical seagrasses, experience considerable spatio-temporal changes in light and other biogeochemical conditions and adopt species-specific acclimatization strategies. Variation in photo-acclimatory responses of three tropical seagrass species (Cymodocea serrulata, Thalassia hemprichii and Enhalus acoroides) were studied by measuring photosynthetic electron transport rates (ETR) using Pulse Amplitude Modulated (PAM) fluorometry technique. Quantitative values of ETR and rates of photosynthetic O2 evolution (net O2 exchange corrected for dark respiration) were compared to establish species-specific relationships in these shallow water conditions. The apparent average molar ratio of O2 evolution to ETR for Cymodocea serrulata, Thalassia hemprichii and Enhalus acoroides were estimated as 0.23, 0.19 and 0.20, respectively. The highest photosynthetic activity (ETRmax) varied significantly among the three studied species in the decreasing order as: E. acoroides (59.27); T. hemprichii (54.06) and C. serrulata (46.72). The effective quantum yield (Y) of PS II (Photosystem II), one of the most useful indicators of stress conditions for seagrass, was observed to be significantly higher for E. acoroides compared to the other two species. Variability of Y in the ambient conditions are explained by the difference in water temperature and pCO2 for the three seagrass species. This study is useful in predicting the photo-acclimation strategies to any change in light availability and subsequent biogeochemical changes at the bottom surface, by these shallow water tropical seagrass species.